OPTIMASI PREVENTIVE MAINTENANCE JIG PADA LINE PROPELLER SHAFT ASSY - , ASWIN NUR RACHMAN; , Ir. Fx. Sukidjo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Condition of jig is very affect the process and outcome of a product. When the jig is undergoing damage so production process will be stop to repairs, but when the jig & fixtures can not be repaired it must be replaced with a new jig, because there is no availability of tools so jig replaced with the old jig that is still considered worthy life and things like this will produce a bad product. To minimize the number linestop, increase production capacity and improve product quality is good, needed a system of care, the preventive maintenance system. jig condition of will be known by checking the entire jig contained on the propeller shaft assy line. When condition of jig is known, so jig availability of has been prepared. Passage of planned preventive maintenance the number of breakdown can be minimized, increased product capacity, and availability of tools that have been prepared.